2018
DOI: 10.1002/aqc.2900
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of salmonid host utilization by the endangered freshwater pearl mussel (Margaritifera margaritifera) in north‐west Scotland

Abstract: 1. The complex life cycle of the globally threatened Margaritifera margaritifera includes a parasitic stage, where glochidia attach to the gills of fishes of the genus Salmo; however, the species of Salmo used appears to vary across its range. In previous literature the reported primary host in Scotland, home to a high proportion of the world's remaining M. margaritifera populations, is the Atlantic salmon Salmo salar, and in its absence the brown trout Salmo trutta.2. In this study, the prevalence of infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
(20 reference statements)
3
12
0
Order By: Relevance
“…The success rate of the infestation procedure was 53%, similar to other experiences which obtained glochidial uptake rates up to 43% (Taeubert & Geist, 2013), although multiple factors may influence this rate, such as the health status of the larvae, its developmental stage and the concentration of larvae in the bath (Lynn, Doerder, Gillis & Prosser, 2018;Meyers & Millemann, 1977;Scheder, Gumpinger & Csar, 2011), or the respiratory rate of fish (Paling, 1968). Regarding the distribution of larvae observed by stereomicroscopy, no preferences were detected for any of the holobranches as described in other M. margaritifera infestations (Clements et al, 2018;Treasurer & Turnbull, 2000;Young & Williams, 1984). most of the glochidia were anchored to the outer area of the filaments, as already suggested by previous studies (Blazek & Gelnar, 2006;Wootten, 1974).…”
Section: Re Sultssupporting
confidence: 68%
See 1 more Smart Citation
“…The success rate of the infestation procedure was 53%, similar to other experiences which obtained glochidial uptake rates up to 43% (Taeubert & Geist, 2013), although multiple factors may influence this rate, such as the health status of the larvae, its developmental stage and the concentration of larvae in the bath (Lynn, Doerder, Gillis & Prosser, 2018;Meyers & Millemann, 1977;Scheder, Gumpinger & Csar, 2011), or the respiratory rate of fish (Paling, 1968). Regarding the distribution of larvae observed by stereomicroscopy, no preferences were detected for any of the holobranches as described in other M. margaritifera infestations (Clements et al, 2018;Treasurer & Turnbull, 2000;Young & Williams, 1984). most of the glochidia were anchored to the outer area of the filaments, as already suggested by previous studies (Blazek & Gelnar, 2006;Wootten, 1974).…”
Section: Re Sultssupporting
confidence: 68%
“…Those facts, along with the premature detachment of larvae during the first month of artificial culture, jeopardize the success of conservation programmes. Nonetheless, there is a paucity of data regarding the most critical stage of the M. margaritifera life cycle and on the host factors that influence the larval survival (Clements, Thomas & Adams, ; Marwaha et al, ; Wacker, Larsen, Karlsson & Hindar, ). In order to elucidate the underlying mechanism involved in the larval attachment and rejection , the purpose of this study was to histologically characterize the gill lesions in S. salar juveniles, together with larval development, during the first weeks of M. margaritifera glochidiosis.…”
Section: Introductionmentioning
confidence: 99%
“…This finding matches what was found in other studies (e.g. Clements, Thomas, & Adams, ) and is likely to reflect a difference in acquired immunity of the older specimens to glochidia through previous infestations (Barnhart et al, ; Kat, ). It is interesting that in infestation experiments of this species with M. auricularia glochidia, no encysted glochidia were found beyond 4 (Araujo et al, ) or 9 (López & Altaba, ) days p.i.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have explored population‐specific differences of Margaritifera margaritifera and found differences in host species suitability in Fennoscandian rivers between populations in large main channels and small tributaries (Salonen et al, ). They have suggested that populations in north‐west Scotland may differ in their cues for attachment to a host (Clements, Thomas, & Adams, ). Population‐specific differences may also exist between mussel populations in the Llano River, which may be more closely adapted to green sunfish from the same river and mussels in the San Saba River, which may be more closely adapted to largemouth bass from the same river; however, further research is needed to explore this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have explored population-specific differences of Margaritifera margaritifera and found differences in host species suitability in Fennoscandian rivers between populations in large main channels and small tributaries . They have suggested that populations in north-west Scotland may differ in their cues for attachment to a host (Clements, Thomas, & Adams, 2018).…”
Section: Discussionmentioning
confidence: 99%